Війна та дезертирство: засади правового регулювання в Україні - Зозуля, І. В.; Zozulia, I. V.; Довгань, О. І.; Dovhan, O. I.; Олена Довгань; Зозуля Ігор (Форум Права. – 2022. – № 2 (73). – С. 60-79, 2022)
Наголошено, що військове дезертирство є всесвітньою проблемою, яка незалежно від обов'язковості чи ні військової служби розглядається як кримінальний злочин і переважно прирівнюється до зради. Здебільшого військовослужбовців до дезертирства спонукають причини, які відносяться до соціально-психологічної сфери діяльності людини, що особливо загострюються під час війни. З введенням в Україні правового режиму воєнного стану та початком широкомасштабної військової агресії росії проти нашої держави особливій увазі надається кримінально-правова складова військового дезертирства, кваліфікуючі ознаки якого закріплені у статті 408 Кримінального кодексу України. Визначено засади правового регулювання в Україні дезертирства як військового злочину напередодні й під час воєнного стану. Встановлено значення бойових та воєнних дій як чинника впливу на рівень дезертирства, досліджено ґенезу інтерпретації дезертирства у вітчизняному законодавстві, визначено особливості військового дезертирства за міжнародною правовою базою та національна правова кваліфікація та сутність військового дезертирства напередодні й під час воєнного стану.

Military desertion is a global problem, which, whether or not military service is mandatory, is regarded as a criminal offense and mostly equated with treason, and therefore requires particular study. Military personnel are motivated to desertion by reasons related to the socio-psychological sphere of human activity, which is especially aggravated during the war. With the introduction of the legal regime of martial law in Ukraine and the beginning of Russia's large-scale military aggression against our state, special attention is paid to the criminal-legal component of military desertion, the qualifying signs of which are enshrined in Article 408 of the Criminal Code of Ukraine, and received some coverage in scientific papers the day before. At the same time, an insufficient number of scientific publications on the legal regulation of desertion as a war crime in Ukraine during martial law are stated. Therefore, the purpose of the article is to determine the basics of legal regulation in Ukraine of desertion as a war crime on the eve of and during martial law. The following methods were used in the work: the dialectical way, with the help of which the values of combat and military actions were established as a factor influencing the level of desertion; methods of system analysis and synthesis in the study of the genesis of the interpretation of desertion in domestic legislation; formal-legal method for determining the features of military desertion in the international legal framework; a comparative legal method for clarifying the differences in the legal qualifications and essence of military desertion on the eve and during martial law. The values of military and military operations as a factor of influence on the level of desertion are established, the genesis of the interpretation of desertion in domestic legislation is investigated, the features of military desertion, according to the international legal framework and the national legal qualification and essence of military desertion on the eve and during the war are determined. It is shown that the legal consequences of the introduction of martial law and the state of war do not affect the statistical level of military desertion as a phenomenon. A more significant influence on the increase in this indicator is exerted by the conduct of combat and military operations in the theater of operations, the socio-psychological state of military personnel, and their assessment of the risks that threaten them. Desertion in domestic criminal law is classified as a serious crime as a deliberate act representing an increased public danger; some of the sanctions against him have changed. It was positive to increase the reporting of the courts on the state of the proceedings on desertion as part of crimes against the established procedure for performing military service (war crimes), as well as laying responsibility for the possible desertion of military personnel on their commanders. Since 2017, deserters, after the completion of the period specified in the instructions, are excluded from the accounting of the personnel of military units. It is shown that military desertion in the international legal framework depends on national legislation. The legal norms in the world on desertion are much broader than in Ukraine and apply to desertion as a deliberate refusal of duties, services, or obligations of a person, especially with military service. It has been determined that the domestic criminal law on crimes against the order of military service needs to be improved due to the accumulation of offenses. The option of turning military commissariats to citizens to search for deserter military personnel did not lead to the expected results, and the norm of suspension of military service for deserters requires additional study during martial law.

Определены принципы правового регулирования в Украине дезертирства как военного преступления накануне и во время военного положения. Установлены значения боевых и военных действий как фактора влияния на уровень дезертирства, исследована генеза интерпретации дезертирства в отечественном законодательстве, определены особенности военного дезертирства по международной правовой базе и национальная правовая квалификация и сущность военного дезертирства накануне и во время войны.
War and desertion: principles of legal regulation in Ukraine
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; воєнний стан; martial law; военное положение; військовий злочин; war crime; военное преступление; дезертирство; desertion; дезертирство; правове регулювання; legal regulation; правовое регулирование; законодавство; legislation; законодательство